Stereotactic Body Radiotherapy as Primary Therapy for Head and Neck Cancer in the Elderly or Patients with Poor Performance - Amini, Arya; McDermott, Jessica D.; Gan, Gregory; Bhatia, Shilpa; Sumner, Whitney; Fisher, Christine M.; Jimeno, Antonio; Bowles, Daniel W.; Raben, David; Karam, Sana D. (Frontiers in Oncology, 2014)
Objective: Stereotactic Body Radiotherapy (SBRT) is increasingly used to treat a variety of tumors, including head and neck squamous cell carcinomas (HNSCC) in the recurrent setting. While there are published data for re-irradiation using SBRT for HNSCC, there are limited data supporting its use as upfront treatment for locally advanced disease. Study Design/Methods: Here we describe three patients who received SBRT as the primary treatment for their HNSCC along with a review of the current literature and discussion of future pathways. Results: The three cases discussed tolerated treatment well with manageable acute toxicities and had either a clinical or radiographic complete response to therapy. Conclusions: HNSCC presents a unique challenge in the elderly, where medical comorbidities make it difficult to tolerate conventional radiation, often given with a systemic sensitizer. For these individuals, providing a shortened course using SBRT may offer an effective alternative.